Transformações do Movimento dos Trabalhadores Rurais Sem Terra – Da Reforma Agrária Ao Certificado De Recebíveis Agrícolas (CRA) - Lima, Matheus Carvalho Assumpção de (2024)
Social movements are of fundamental importance for the effective articulation of demands in the face of the first sector (government) and are essential in a demo-cratic society, as they enable the expansion of discussions on public policies that are beneficial for part of the population. From this perspective, the action of social movements aimed at demanding agrarian reform, especially the MST, is necessary in Brazilian territory, as it is a country that, admittedly, prioritizes large estates to the detriment of family farming. That said, this work focused on the entire history of the MST's actions, considering historical precedents, its creation, chronological evolution of narratives and demands, taking as a basis, especially, publications made in the media (sem-terra newspaper, newsletters, Movement website, etc.). Furthermore, the way in which the Movement raised financial resources over the years was also an object of study. In this regard, it is essential to analyze the forms of action of the MST and the details of the MST's communication. And, finally, an assessment of possible internal dissonances between the MST as an institution and the settlers and peasant workers.